The Implementation of the Islamic Personal Development Program in Cultivating Students' Noble Character at SMP IT Fitrah Hanniah - Salma Rahma Dina; Syahidin Syahidin; Mulyana Abdullah (Seutia Hukamaa Cendekia, 2026)
Modern education faces the challenge of moral degradation, which demands character interventions beyond classical approaches. This study aims to examine the managerial mechanisms of the Islamic Personal Development Program at SMP IT Fitrah Hanniah, which serves as a holistic ecosystem for moral cultivation. Employing a qualitative case-study design, data were extracted from multi-actor interviews, small-group participatory observations, and evaluation documentation and subsequently analyzed using an interactive reduction scheme. The findings confirm that stable character formation is realized through three managerial reconfigurations. In the planning phase, the curriculum is centrally controlled by the foundation, which tactically restructures the class into small groups of up to ten 10 students. During the implementation phase, the program shifts away from cognitive transmission orientation to prioritize emotional bonding and exemplary imitation through varied educative methods. In the evaluation phase, the school exclusively uses observation-based qualitative assessments and daily track records, followed by educational disciplinary measures. The conclusion of this study asserts that internal governance reconfigurations are proven effective in instilling discipline in daily worship. However, the ultimate manifestation of social morality strictly requires the reinforcement of supervisory synergy from parents to sustain behavioral habits outside school hours. Consequently, these findings recommend a more binding model of family involvement within the governance of character education.